The Influence of Exports and Islamic Bank Financing on Economic Growth in North Sumatra Province - Daei, Muhammad Imam; Imsar, Imsar; Syahbudi, Muhammad (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the effect of exports and Islamic bank financing on the economic growth of North Sumatra Province using monthly time series data from 2013 to 2022. The research employs a quantitative approach, with data processed using EViews 12 and analyzed through the Vector Autoregression (VAR) and Vector Error Correction Model (VECM) methods to examine both short-term and long-term relationships among variables. The findings indicate the existence of long-term equilibrium among exports, Islamic bank financing, and economic growth. However, in the short term, neither exports nor Islamic bank financing have a statistically significant effect on economic growth, although a unidirectional causality is observed from economic growth to both variables. The impulse response analysis reveals fluctuations in both variables’ reactions to economic growth shocks during the early periods. In the long run, exports show a more dominant and significant influence on economic growth compared to Islamic bank financing. These results highlight the need for strategic efforts to enhance export performance and optimize the role of Islamic banking in supporting regional economic growth.